Imperfect Production Inventory Models: A Bibliometric Analysis - Novrianty Rizky; Agham Satria Pristiwaji; Muhammad Ridwan Andi Purnomo (Institute of Computer Science (IOCS), 2022)
Economic order quantity models have been fascinated to be researched since a long time ago. This article presents a bibliometric analysis for imperfection production inventory models. Analysis involved 40 peerreviewed research articles published during 2000-2020 at Google Scholar and Sciencedirect. The articles are filtered based on trends, year of publication, countries, institution, and publisher name. Result of this study shows that a journal entitled International Journal of Production Economics has the most published article in the area. Content analysis has classified purpose of research, type of echelon, type of demand, lead-time, backorder, type of production process, quality improvement, setup cost and ordering cost reduction, logistic cost, and pick-up service. This study also recommends research gap for future studies in the field of inventory for supply chain management